ANALYZING THE SMOOTH AND STRIATED SPACE IN PASAR CIPUTAT TANGERANG SELATAN - Eka Permanasari; Bonardo Tobing (Diponegoro University, 2018)
Striated is seen as a fixed space and carries a sense of border. On the other hand, smooth space is seen as continuous and open interval. However, both terms are always intermingling, at one point smooth can be striated and vice versa. A city can be seen as a striated (border) and as smooth space (urban sprawl). Looking at a strip near Pasar Ciputat, Tangerang Selatan, this paper investigates how space changes function and identity overtime. The strip becomes a good example of analyzing the smooth and striated space practiced in everyday life. This strip is heavily populated by street vendors who has ‘occupying schedule’ and continuously changes the patterns of occupation. They prefer to sell goods on the road instead of in the provided building. By midnight, the road is not accessible as the vendors closed off and sell their goods on the road. In the morning and afternoon, some vendors disappear and their former space has been used by other vendors to sell different goods. Through observation, urban morphological mapping and photographic analysis, this paper uncovers the fluid uses and meaning of the space.